Interpreting regional frequencies from synchronized phasor measurement in multi-area power systems - Vahidnia, A.; Ledwich, G.; Palmer, E.; Ghosh, Arindam (Institute of Electrical and Electronics Engineers ( IEEE ), 2011)
In this paper a new approach is proposed for interpreting of regional frequencies in multi machine power systems. The method uses generator aggregation and system reduction based on coherent generators in each area. The reduced system structure is able to be identified and a kalman estimator is designed for the reduced system to estimate the inter-area modes using the synchronized phasor measurement data. The proposed method is tested on a six machine, three area test system and the obtained results show the estimation of inter-area oscillations in the system with a high accuracy